LEGAL VIOLATION REGIME IN THE STATE AIRSPACE AGAINST CIVIL AIRCRAFTS IN FLIGHT - Волостних, Володимир Сергійович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: this article defines the legal violation regime in the sovereign state airspace against civil aircrafts in flight based on the documents developed within the International Civil Aviation Organization. There are described the measures which could and have to be undertaken on interception of a civil aircraft by the state aviation. Methods: the author gives an assessment of the legal regime for the use of force against civil aircraft in flight, practical steps are proposed to resolve the issue under consideration. Discussion: there is a conclusion about the necessity of development of domestic space law.